Exploring the potential of an audio application for teaching AI-based classification methods to a wider audience - Coto-Fernández, Gabriel (2022)
Knowledge about artificial intelligence (AI) is becoming increasingly important for many careers, especially those based in science and engineering. Besides formal education, the impact of AI on society lead to consider educational projects for teaching the fundamental concepts of AI at wider audiences, including high school levels. This can help more general audiences to better understand how AI works, with the hope that also parents and educators can help students develop a healthy appreciation for implications and limitations, along with an appropriate relationship and deeper interest on it. In this paper, we present a pilot project for teaching an AI-based classification method that is empirically evaluated with real data of a real problem, which can be understood and tackled with basic mathematical tools and activities suitable for high school students. With this proposal, we aim to show how audio and speech applications can inform a wider audience about advances in AI, its characteristics, and its future impact on society. Results and lessons learned from this project can form the basis for further projects using different tools and data, according to students’ interests and initiative.